Presence of multiple lesion types with vastly different microenvironments in C3HeB/FeJ mice following aerosol infection with Mycobacterium tuberculosis - Scott M. Irwin; Emily Driver; Edward Lyon; Christopher Schrupp; Gavin Ryan; Mercedes Gonzalez-Juarrero; Randall J. Basaraba; Eric L. Nuermberger; Anne J. Lenaerts (The Company of Biologists, 2015)
Cost-effective animal models that accurately reflect the pathological progression of pulmonary tuberculosis are needed to screen and evaluate novel tuberculosis drugs and drug regimens. Pulmonary disease in humans is characterized by a number of heterogeneous lesion types that reflect differences in cellular composition and organization, extent of encapsulation, and degree of caseous necrosis. C3HeB/FeJ mice have been increasingly used to model tuberculosis infection because they produce hypoxic, well-defined granulomas exhibiting caseous necrosis following aerosol infection with Mycobacterium tuberculosis. A comprehensive histopathological analysis revealed that C3HeB/FeJ mice develop three morphologically distinct lesion types in the lung that differ with respect to cellular composition, degree of immunopathology and control of bacterial replication. Mice displaying predominantly the fulminant necrotizing alveolitis lesion type had significantly higher pulmonary bacterial loads and displayed rapid and severe immunopathology characterized by increased mortality, highlighting the pathological role of an uncontrolled granulocytic response in the lung. Using a highly sensitive novel fluorescent acid-fast stain, we were able to visualize the spatial distribution and location of bacteria within each lesion type. Animal models that better reflect the heterogeneity of lesion types found in humans will permit more realistic modeling of drug penetration into solid caseous necrotic lesions and drug efficacy testing against metabolically distinct bacterial subpopulations. A more thorough understanding of the pathological progression of disease in C3HeB/FeJ mice could facilitate modulation of the immune response to produce the desired pathology, increasing the utility of this animal model.